THE ROLE OF COOPERATION AND SMEs DEPARTMENT IN EFFORTS TO DEVELOP MSME PRODUCTS THROUGH THE “UMKM JUARA” PROGRAM IN SUKABUMI CITY - Nenden Tari Fithriati; Rizki Hegia Sampurna; M. Rijal Amirulloh (DIA: Jurnal Administrasi Publik, 2024)
Micro, Small and Medium Enterprises are an important sector and have a large contribution in realizing regional economic development. In this case, it contributes 60 percent to GDP and is able to absorb labor up to 97.22 percent. Therefore, the West Java Provincial government created a program "UMKM Juara" to empower MSMEs. The purpose of this study is to find out how the role of the Cooperative and SMEs Office in efforts to develop MSME products through the "UMKM Juara" program in Sukabumi City. Researchers used the theory of Gede Diva, 2009 regarding the role of government as a facilitator, regulator, and catalyst. The results showed that the local government has done its job well in terms of facilitators, regulators and catalysts, however, there are still shortcomings in terms of MSME participant targets that have not been achieved and the lack of budget for the program that will be implemented.